キョクチ データベース システム ノ カイハツ - 岩渕, 美代子; イワブチ, ミヨコ; 桜井, 治男; サクライ, ハルオ; 宮本, 一治; ミヤモト, カズハル; IWABUCHI, Miyoko; SAKURAI, Haruo; MIYAMOTO, Kazuharu (国立極地研究所, 1978)
P(論文) 1976年末,国立極地研究所への電子計算機HITAC M-160 II導入に伴って計画され,建設された極地データベースシステムについて,その概要を示す.極地データベースシステムは,観測データ,地図データ,文献データの3つから構成される.それぞれのデータの内容と利用法の概略を,使用例をあげて示す. A polar data-base system by means of HITAC M-160 II computer has been constructed at the National Institute of Polar Research. The system consists of three kinds of data; data obtained by the Japanese Antarctic Research Expedition, digital world map data including Antarctic maps and Antarctic bibliography data. Users can easily combine the two kinds of these data by the use of Fortran language. Some examples of combination are shown. departmental bulletin paper